PENGARUH KOMPETENSI DAN INDEPENDENSI TERHADAP EFEKTIVITAS SPIP DENGAN PENGALAMAN KERJA APIP SEBAGAI VARIABEL INTERVENING PADA INSPEKTORAT PEMERINTAH PROVINSI SUMATERA UTARA - Ulya, Shafira Hidayah; Sari, Eka Nurmala; RS, Prawidya Hariani (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
The purpose of this study was to determine, test and analyze the effect of competence on the effectiveness of SPIP, the effect of independence on the effectiveness of SPIP, the effect of APIP’S work experience on the effectiveness of SPIP, the influence of competence on the effectiveness of SPIP through APIP’s work experience and the influence of independence on the effectiveness of SPIP through APIP’s work experience. The type of research in this study is quantitative research with an associative approach using primary data and data collection techniques through distributing questionnaires to the inspectorate of the provincial government of north sumatera, Indonesia. The population of this study were all government internal supervisory officerseho served in the inspectorate of the government of north sumatera province totaling 680 people. The method of determining the sample is the proportional stratified random sampling method which is taken randomly and stratified using the slovin formula. The sample in this study was 87 people. The data was processed using the SEM method with the help of the Smart PLS analysis tool. The results of this study prove that there is an influence of competence on the Effectiveness of SPIP, the influence of Independence on the Effectiveness of SPIP, the influence of APIP's Work Experience on the Effectiveness of SPIP, the influence of Competence on the Effectiveness of SPIP through APIP's Work Experience and the influence of Independence on the Effectiveness of SPIP through APIP's Work Experience.